Clindamicina inibe a resposta nociceptiva em modelos de dores aguda e crônica por meio da ativação de mecanismos opioidérgicos e serotoninérgicos - Felipe Fernandes Rodrigues (2017)
Clindamycin is a lincosamide antibiotic used to treat patients with pneumonia, osteomielitis and skin infections. It has been recently demonstrated that clindamycin inhibits TNF-, IL-1 and prostaglandins production. Thus, the present study aimed to investigate the activity of clindamycin in models of nociceptive and inflammatory pain and inflammatory edema in mice. Clindamycin (200 and 400 mg/kg, i.p.) inhibited the paw edema and mechanical allodynia induced by carrageenan (400 g/20 L, i.pl.) for at least 6 h. Clindamycin (200 and 400 mg/kg, i.p.) inhibited the paw edema induced by formaldehyde, while only the highest dose (400 mg/kg, i.p.) inhibited the second phase of the nociceptive response induced by this inflammatory stimulus. In the model of nociceptive response induced by heat (hot plate), only the highest dose (400 mg/kg, i.p.) increased the latency for the nociceptive behavior. Treatment with clindamycin (100, 200 and 400 mg/kg, i.p.), in the first and seventh day after injection of CFA (1 mg/mL, 20 l, i.pl.), reduced the paw edema and mechanical allodynia for at least 48 h. Administration of clindamycin (400 mg/kg), every 72 h, markedly reduced the paw edema and mechanical allodynia induced by CFA. Clindamycin (400 mg/kg, i.p.) reduced the concentration of TNF- in the paw of animals that received an i.pl. injection of CFA, but not carrageenan. The motor activity of the animals was not affected by clindamycin. The activity of clindamycin in the model of nociceptive pain induced by heat was reduced by previous administration of naltrexone (5 e 10 mg/kg, i.p.) and ciproheptadine (5 e 10 mg/kg, p.o.), but not by glibenclamide (20 e 40 mg/kg, p.o) and AM251 (4 e 8 mg/kg, i.p.). Concluding, the results demonstrate the activity of clindamycin in models of acute nociceptive and inflammatory pain, chronic inflammatory pain, as well as in models of acute and chronic inflammatory edema. In models of chronic inflammation, the antiallodynic and antiedematogenic activities were demonstrate even after the establishment of sensitization and paw edema. These activities are probably associated with inhibition of the production or action of inflammatory mediators. The results also indicate that opioidergic and serotonergic mechanisms may mediate the antinociceptive activity of clindamycin. Altogether, the results indicate that clindamycin may be further investigated aiming its repositioning in the treatment of patients with inflammatory and painful conditions.